Effect of Lycopene Supplementation on Some Cardiovascular Risk Factors and Markers of Endothelial Function in Iranian Patients with Ischemic Heart Failure: A Randomized Clinical Trial. (28th October 2022) - Karimian, Bahareh; Soleimani, Azam; Mohammadsharifi, Ghasem; Heshmat-Ghahdarijani, Kiyan; Rejali, Laila; Shafie, Davood; Amerizadeh, Atefeh; Sadeghi, Masoumeh
Abstract : Aim . This study aimed to explore if supplementary lycopene tablets may help heart failure (HF) patients improve their lipid profile, BP, and the flow-mediated dilation (FMD) index for endothelial function. Methods . Fifty patients with ischemic HF with a reduced ejection fraction (HFrEF) were randomly assigned to one of two groups: the lycopene group which received 25 mg lycopene tablets once a day for 8 weeks and the control group which received placebo tablets containing starch once a day for 8 weeks. Results . Our results showed that after two months, the amount of triglyceride (TG) and FMD improved significantly compared to the control, TG decreased (219.27 vs. 234.24), and the mean of FMD increased (5.68 vs. 2.95). Other variables, including total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density cholesterol (HDL-C), systolic blood pressure (SBP), and diastolic blood pressure (DBP), showed no improvement. Also, only SBP and FMD showed intragroup improvement in the intervention group. In the intervention group, only SBP and FMD exhibited intragroup improvement. Conclusions . It can be concluded that supplementing with lycopene can enhance endothelial function and reduce the TG levels in ischemic HFrEF patients. However, it had no positive effect on BP, TC, LDL-C, or HDL-C. Trial Registration . This clinical trial was registered at the Iranian Registry of Clinical Trials with IRCT registration number: IRCT20210614051574N4 .